‘Everybody has to be accountable’: calling out and dragging practice among university youths in Nigeria - Oni, Sharon Damilola; Ojedokun, UsmanUsman Adekunle; Aderinto, Adeyinka Abideen (Przegląd Krytyczny, 2023)
Calling out and dragging practice has emerged as one of the dominant popular cultures among Nigerian youths owing to the ubiquity of social media platforms. However, despite the growing acceptability of calling out and dragging among the youths, empirical research focusing on this online practice are generally rare. Therefore, this study investigated University of Ibadan undergraduates’ conceptions and dispositions towards calling out and dragging on Twitter. The theory of reasoned action was employed as the conceptual framework, while data were primarily sourced from 318 undergraduates who were selected through the multistage sampling technique. Survey questionnaires and in-depth interview methods were strategically combined for the purpose of data elicitation. Results showed that the majority of the respondents (64%) conceived calling out and dragging as the tagging of the depraved members of society. Although the most significant single share (55.5%) identified celebrities as the category of people frequently called out and dragged on Twitter, most of them (55.9%) mentioned religious issues as the trending topic they usually consciously avoided. Calling out and dragging is an online practice that needs to be moderated because of its potential multiple social ramifications.